Modern tendencies and directions of improvement constructions baskets of railway freight gondolas - Фомін, Олексій Вікторович (Technology audit and production reserves, 2012)
In the article features of scientific and technical works are presented on the improvement baskets of railway freight gondolas and going near their planning